The Effectiveness Of Patt_Art Media Based On Digital Literation In Introducing Mathematical Concepts For Early Ages - Naili Rohmah; Mohamad Hariyono; Erna Zumrotun (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2020)
Branches of mathematics introduced by early childhood include: counting, numerating, geometry, measuring, estimating, patterns, and statistics. Unfortunately, the activity of introducing patterns in Early Age Education (PAUD) institutions still uses traditional media. The introduction of patterns that are part of the mathematical concepts at PAUD institutions must keep abreast of the times. The current development is in the digital era that allows all activities carried out by children integrated with digital media. The current digital era demands all components of society to be aware of digital literacy, including early childhood (AUD). This research is important to do, because of the lack of pattern recognition media for children, so that the results of Patt_art media development will be useful as an alternative media pattern recognition. This study aimed to examine the effectiveness of digital literacy-based Patt_art media in introducing mathematical abilities of early childhood. The research method used experimental research methods. RA NU Matholibul Ulum 01 became the experimental group and RA NU Matholibul Ulum 02 became the control group. Data collection techniques to be performed used observation techniques and oral tests. Data analysis techniques used paired sample t test. The results show that: 1) the learning outcomes of the experimental group were higher than the control group; and 2) Patt_Art media is more effective than conventional media.